Potent and tumor specific: arming bacteria with therapeutic proteins. (April 2015) - Van Dessel, Nele; Swofford, Charles A; Forbes, Neil S
Bacteria are perfect vessels for targeted cancer therapy. Conventional chemotherapy is limited by passive diffusion, and systemic administration causes severe side effects. Bacteria can overcome these obstacles by delivering therapeutic proteins specifically to tumors. Bacteria have been modified to produce proteins that directly kill cells, induce apoptosis via signaling pathways, and stimulate the immune system. These three modes of bacterial treatment have all been shown to reduce tumor growth in animal models. Bacteria have also been designed to convert nontoxic prodrugs to active therapeutic compounds. The ease of genetic manipulation enables creation of arrays of bacteria that release many new protein drugs. This versatility will allow targeting of multiple cancer pathways and will establish a platform for individualized cancer medicine.